2022
DOI: 10.3390/ma15051891
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Properties of Three Resin-Based Dental Composites against Streptococcus mutans

Abstract: Antibacterial and antibiofilm properties of restorative dental materials may improve restorative treatment outcomes. The aim of this in vitro study was to evaluate Streptococcus mutans capability to adhere and form biofilm on the surface of three commercially available composite resins (CRs) with different chemical compositions: GrandioSO (VOCO), Venus Diamond (VD), and Clearfil Majesty (ES-2). Disk-shaped specimens were manufactured by light-curing the CRs through two glass slides to maintain a perfectly stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Another study found that a composite resin that did not contain Bis-GMA showed significantly higher adhesion to S. mutans than other Bis-GMA-based resins [33]. Nev-ertheless, Bis-GMA should not be regarded as the only factor affecting bacterial adhesion, as all components of the composite resin can interact with each other, and the combinations can also be one of the influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that a composite resin that did not contain Bis-GMA showed significantly higher adhesion to S. mutans than other Bis-GMA-based resins [33]. Nev-ertheless, Bis-GMA should not be regarded as the only factor affecting bacterial adhesion, as all components of the composite resin can interact with each other, and the combinations can also be one of the influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Surface modification could be a possible approach to identify surfaces that possess anti-biofilm properties [ 22 ]. The injection mode is precise and too short in duration, yet it depends on conditions and factors that could be manipulated, and the injection molding devices allow for it.…”
Section: Discussionmentioning
confidence: 99%
“…It is designed for use in complete or partial denture bases, bridge constructions, and temporary crowns. Comprising microcrystalline polyamide material with pigments, it becomes a suitable option for patients with monomer allergies [26,27]. The molding process for Vertex ThermoSens involves an injection technique, which can be performed using automatic or manual injection machines [28,29].…”
Section: Introductionmentioning
confidence: 99%